Robotic posterior retroperitoneal adrenalectomy versus laparoscopic posterior retroperitoneal adrenalectomy: outcomes from a pooled analysis - Li, Yu-gen; Chen, Xiao-bin; Wang, Chun-mei; Yu, Xiao-dong; Deng, Xian-zhong; Liao, Bo (Frontiers in Endocrinology, 2023)
The comparative advantages of robotic posterior retroperitoneal adrenalectomy (RPRA) over laparoscopic posterior retroperitoneal adrenalectomy (LPRA) remain a topic of ongoing debate within the medical community. This systematic literature review and meta-analysis aim to assess the safety and efficacy of RPRA compared to LPRA, with the ultimate goal of determining which procedure yields superior clinical outcomes.A systematic search was conducted on databases including PubMed, Embase, Web of Science, and the Cochrane Library database to identify relevant studies, encompassing both randomized controlled trials (RCTs) and non-RCTs, that compare the outcomes of RPRA and LPRA. The primary focus of this study was to evaluate perioperative surgical outcomes and complications. Review Manager 5.4 was used for this analysis. The study was registered with PROSPERO (ID: CRD42023453816).Results: A total of seven non-RCTs were identified and included in this study, encompassing a cohort of 675 patients. The findings indicate that RPRA exhibited superior performance compared to LPRA in terms of hospital stay (weighted mean difference [WMD] -0.78 days, 95% confidence interval [CI] -1.46 to -0.10; p = 0.02).However, there were no statistically significant differences observed between the two techniques in terms of operative time, blood loss, transfusion rates, conversion rates, major complications, and overall complications.Conclusions: RPRA is associated with a significantly shorter hospital stay compared to LPRA, while demonstrating comparable operative time, blood loss, conversion rate, and complication rate. However, it is important to note that further research of a more comprehensive and rigorous nature is necessary to validate these findings.